Community Responses toward COVID-19 Pandemic: An Online Survey Study - Abd. Gani Baeda; Muhdar Muhdar; Grace Tedy Tulak; Rosani Naim; Rosmiati Rosmiati; Heriviyatno Julika Siagian (Media Kesehatan Masyarakat Indonesia, 2020)
COVID-19 has become a frightening pandemic and has spread throughout theworld with an unprecedentedly high death rate. Community compliance withgovernment appeals must be accompanied by knowledge, attitudes, and practicesin dealing with this epidemic. This study aims to investigate the Knowledge,Attitude, and Practice of Kolaka residents against the COVID-19 outbreak. Thisresearch is descriptive-analytic with a Cross-Sectional approach. The sample usedin this study were 1,010 respondents aged 17 to 65 years, having gmail and y-mail accounts, mastering the internet became the criteria for respondentinclusion in this study. The questionnaire used was the adoption of previousstudies and modified according to conditions. Data were analyzed bivariate usingthe Chi-Square test with standard p-value<0.05. The results obtained showed thatthe Kolaka community had good knowledge (49.6%), a confident attitude ofcontrolling the plague (70.4%), and had a high level of vigilance (79.6%) towardsCOVID-19. There is a relationship between knowledge with practice p-value=0.000, while attitude has no relationship with practice with p-value=0.862.The massive dissemination of information through existing media has greatlyhelped the community increase their knowledge of COVID-19, which will furthersupport the formation of a confident attitude to control this disease and increasevigilance in their daily life practices during this pandemic.